A Prospective Investigation of Bispecific CD19/22 CAR T Cell Therapy in Patients With Relapsed or Refractory B Cell Non-Hodgkin Lymphoma - Zhang, Ying; Li, Jiaqi; Lou, Xiaoyan; Chen, Xiaochen; Yu, Zhou; Kang, Liqing; Chen, Jia; Zhou, Jin; Zong, Xiangping; Yang, Zhen; Li, Minghao; Xu, Nan; et al. (Frontiers in Oncology, 2021)
Background The use of T cells expressing chimeric antigen receptor (CAR T) engineered to target CD19 constitutes breakthrough treatment for relapsed or refractory B cell non-Hodgkin lymphoma (R/R B-NHL). Despite improved outcomes, high relapse rate remains a challenge to overcome. Here, we report the clinical results and the pharmacokinetics of bispecific CD19/22 CAR T in patients with R/R B-NHL. Methods We performed a prospective, single-arm study of bispecific CD19/22 CAR T cells in R/R B-NHL. We analyzed the safety and efficacy and investigated the kinetic profiles of the CAR T cells. CAR transgene levels were measured using quantitative polymerase chain reaction, and correlation analyses of pharmacodynamic markers and product characteristics, disease conditions, clinical efficacy and adverse events were performed. Results From August 2017 to September 2020, a total of 32 patients with CD19/22 CAR T administration were analyzed. The overall response rate was 79.3%, and the complete response rate was 34.5%. The progression-free survival (PFS) and overall survival (OS) rates at 12 months were 40.0% and 63.3%, respectively. Among patients who had a CR at 3 months, the PFS and OS rates at 12 months were 66.7% and 100%, respectively. Severe cytokine release syndrome (sCRS) (grade 3 and higher) occurred in nine patients (28.1%). Grade 3 or higher neurologic events occurred in four patients (12.5%). One patient died from irreversible severe CRS-associated acute kidney injury. Long-term CAR T cells persistence correlated with clinical efficacy (133 days vs 22 days, P = 0.004). Patients treated with more than three prior therapies and presenting extranodal organ involvement had lower maximal concentration (Cmax) values than other patients. Responders had higher Cmax and area under the curve values than non-responders. Tumour burden and Cmax were potentially associated with the severity of CRS. Conclusions This study demonstrates the safety and potential clinical efficacy of bispecific CD19/22 CAR T cells in patients with R/R B-NHL and highlights the importance of measuring kinetic parameters in PB to predict efficacy and safety in clinical applications of CAR T cell therapy. Clinical Trial Registration https://www.clinicaltrials.gov/ct2/show/NCT03196830, identifier NCT03196830.